Knitting Tradition and Mathematics: Systematizing the Literature on Indonesian Traditional Games and Mathematical Dimensions - Transita Pawartani; Suyono Suyono; Intan Sari Rufiana; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (STAI Hubbulwathan Duri, 2024)
Mathematics presents significant learning challenges for students globally, which is often reflected in poor academic performance. This research explores the potential of traditional Indonesian games to enhance math learning, an under-explored approach that can also contribute to cultural preservation This research investigates how traditional Indonesian games can enhance math learning. We conducted a Systematic Literature Review, selecting articles through keyword searches in the Google Scholar database. The criteria used were articles on Indonesian traditional games. The result of this study is that traditional Indonesian games can enhance math learning by: (1) Presenting a strong rationale that the use of Indonesian traditional games in mathematics learning is often motivated by difficulties in learning mathematics as well as cultural preservation; (2) Integrating traditional games in mathematics learning according to students' characteristics, especially at the elementary level; (3) Applying relevant mathematics topics, such as geometry and number, in traditional games; (4) Integrating traditional games that are widely known by students, such as engklek and congklak, in mathematics learning; (5) Apply the presentation technique of integrating traditional games and mathematics through learning activities at school with teachers; (6) Realize that the integration of traditional games in mathematics learning affects students' affective, cognitive, psychomotor, and skill abilities that will improve their mathematics abilities.